Generation of three-qubit entangled W-state by nonlinear optical state truncation - Said, Ressa Suhardiman; Wahiddin, Mohamed Ridza; Umarov, Bakhram A. (Institute of Physics Publishing (IOP), 2006)
We propose an alternative scheme to generate the W state via optical state truncation using quantum scissors. In particular, these states may be generated through three-mode optical state truncation in a Kerr nonlinear coupler. The more general three-qubit state may also be produced if the system is driven by external classical fields.